COMPARATIVE STUDY ON SOME PHONOLOGICAL FEATURES OF STANDARD ASSAMESE AND NALBARIA DIALECT - Rahman, Md. Wahidur (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Up to 17th century the Kamrupi dialect had special influence on the field of literature and culture of Assam. Subsequently, the influence of Kamrupi language decreased due to the political and social factors. Before the coming of the British, the lower Assam region, especially undivided Kamrup district was the centre of literary exercises and scholarly activities. But a new literary language originated in the middle of the 19th century when the American Baptist Missionaries started publishing 'Arunodoi' using the local dialects of Sibsagar region. Consequently dialect of Sibsagar was standardized as standard Assamese and the Assamese language of Kamrupa becomes lesser known dialect and it has been confined to the spoken language of the greater Kamrup region. The spoken language of Kamrup, Nalbari, Baksa and Barpeta districts of undivided Kamrup district is regarded as Kamrupi dialect. The spoken variety of Nalbari region called as Nalbaria dialect is a branch of Kamrupi dialect. Nalbaria dialect exhibits certain homogeneity like, use of tripthong, frequent use of apenthetic vowel etc. which are not found in standard Assamese. The final diphthongs/oi/ and /ou/ of standard Assamese generally appear as / e/ and /o/ in Nalbaria dialect. This paper attempts to highlight some phonological differences between standard Assamese and Nalbaria dialect and it attempts to describe some phonological features of standard Assamese and Nalbaria dialect in comparative terms.